Religion and the State in Tanzania and Malawi - Forster, Peter G. (Journal of Asian and African studies, 1997)
Abstract Relations between religion and the state can be particularly problematic in Africa, and recent events in Tanzania and Malawi confirm this. The first post-independence governments of both countries expected religious values to support state ideology more or less uncritically, in return for religious freedom. More recent events in both countries have led to lessening of identity between state and religious values. Broader issues of rivalry of religion and state for ultimate support; the political dimension of moral concern; and the lack of identity between religious and political boundaries are all seen to be relevant.